Comparative lipidomics analysis of different-sized fat globules in sheep and cow milks - Pan Z; Ye A; Fraser K; Li S; Dave A; Singh H (Elsevier B V, 2024)
The effect of milk fat globule (MFG) size and species (sheep versus cow) on the lipid and protein compositions of sheep and cow milks was studied. The MFGs in raw cow and sheep milks were separated into six significantly different-sized (1.5-5.5 μm) groups by a gravity-based separation method, and their fatty acids, their lipidomes and the protein compositions of their MFG membranes were determined. The proportions of polar lipids increased but glycoproteins decreased with decreasing MFG size in both sheep milk and cow milk; the fatty acid composition showed few differences among the MFG groups. The average size of each MFG group was comparable between sheep milk and cow milk. Sheep milk contained higher proportions of short-chain fatty acids, medium-chain fatty acids and sphingomyelin than cow milk in all MFG groups. The proportion of glycoproteins was higher in cow MFG membrane than in sheep MFG membrane. The results suggested that the lipid and protein compositions were markedly species and size dependent.
Keywords: Fatty acid; Glycoprotein; Lipidome; Milk fat globule membrane; Phospholipids; Polar lipids